Continuous Dependence of the Solutions of Nonlinear Integral Quadratic Volterra Equation on the Parameter. (23rd February 2015) - Dudek, Szymon; Olszowy, Leszek
Abstract : We prove results on the existence and continuous dependence of solutions of a nonlinear quadratic integral Volterra equation on a parameter. This dependence is investigated in terms of Hausdorff distance. The considerations are placed in the Banach space and the Fréchet space.